Eating in the absence of hunger is not associated with weight, self-reported eating behaviors, or well-being in pregnant adults: Prospective cohort study - Leah M. Lipsky; Kyle S. Burger; Myles S. Faith; Grace E. Shearrer; Tonja R. Nansel (PLoS ONE, 2025)
Objective Eating in the absence of hunger (EAH) refers to consuming food after reaching satiation and is considered a risk factor for weight gain. This study examined relations of EAH with pregnancy-related weight outcomes, self-reported eating behaviors, and indicators of well-being. Methods EAH was measured in participants (n = 46) during their 2nd pregnancy trimester. Energy intake and percent of food consumed following a standardized meal was calculated for all foods, and separately for sweet (desserts) and savory (salty snacks) foods. Early pregnancy BMI, gestational weight gain, and postpartum weight change were calculated from measured height and weight from <12 weeks gestation to 1 year postpartum. Participants reported eating behaviors (Dutch Eating Behavior Questionnaire), depressive symptoms (Edinburgh Postnatal Depression Scale), stress (Perceived Stress Scale), and sleep quality (Pittsburgh Sleep Quality Index) < 28 weeks gestation. Linear and logistic regression models estimated relationships between the variables of interest. Results Primarily null estimates did not provide consistent evidence of associations of eating behaviors or indicators of well-being with EAH, or of EAH with pregnancy-related weight outcomes. Conclusions EAH in pregnancy was not related to weight change, eating behaviors, depressive symptoms, sleep quality, or stress. Future studies in larger samples and diverse developmental periods are needed to determine the utility of laboratory-assessed EAH as a risk factor for weight gain. Trial registration ClinicalTrials.gov NCT02217462